Phytoremediation of Mercury Contaminated Soil with the Addition of Compost - Rhenny Ratnawati; F. Faizah (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
Phytoremediation is an alternative technology for processing mercury (Hg) contaminated soil. The objective of this study was to treat Hg contaminated soil by adding compost using Sansevieria trifasciata and Celosia plumosa. The variations of the composition of the growth media were 100% contaminated soil and 80% contaminated soil with 20% compost. The plants used were aged 1 month and 30 cm high. The reactor was a polybag with a diameter and height of 25 cm. Sampling was conducted once every 7 days for 28 days. This research showed that the reactor with growth media consisting of 80% contaminated soil and 20% compost with Sansevieria trifasciata and Celosia plumosa had an Hg removal efficiency of 75.63% (58 mg/kg) and 66.81% (79 mg/kg), respectively. The Hg removal efficiency with growth media consisting of 100% contaminated soil was 74.79% (60 mg/kg) and 65.55% (82 mg/kg) in the reactor with Sansevieria trifasciata and Celosia plumosa respectively.